Montagem de um aparato experimental para estudo de interações entre duas bolhas alongadas de ar escoando em líquido estagnado em um tubo vertical - Auer, Klisman (2025)
Multiphase flows occur in several industrial applications, and their understanding is essential to improve the various processes carried out in such applications. Empirical knowledge plays a significant role in understanding these flows, their phase configurations, and their consequences. Thus, the present work aims to assemble and test an experimental apparatus to study elongated air bubbles flowing in stagnant liquid (water) in vertical pipes. The apparatus consists of a structure of aluminum profiles to support acrylic pipes (test section) measuring 6 m in length and 26 mm in internal diameter, in addition to two devices (for releasing bubbles and filling liquid) between others. This configuration should allow the observation and analysis of the behavior of such gas-liquid flows under different conditions. Notably, the experimental apparatus was designed to be cost-effective, easy to operate, and adaptable to different experimental setups. The development of simplified methodologies for assembly and use further increases their usefulness in various applications in pipe flow studies. The tests demonstrated that the system effectively advances the understanding of relevant phenomena of multiphase flows.